Loneliness, Anxiety and Depression among Patients with Epilepsy - Beata Dziedzic; Adrianna Kalinowska; Ewa Kobos; Zofia Sienkiewicz; Wiesław Fidecki; Mariusz Wysokiński (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Epilepsy is one of the most common neurological disorders. The unpredictability of epileptic seizures can lead to feelings of loneliness, social isolation and stigmatisation. Due to the nature of this syndrome, patients may also show symptoms of depression.